Sphingolipid signaling in metabolic disorders - Hla, Timothy (2012)
Sphingolipids, ubiquitous membrane lipids in eukaryotes, carry out a myriad of critical cellular functions. The past two decades have seen significant advances in sphingolipid research and in 2010, a first sphingolipid receptor modulator was employed as a human therapeutic. Further, cellular signaling mechanisms regulated by sphingolipids are being recognized as critical players in metabolic diseases. This review focuses on recent advances in cellular and physiological mechanisms of sphingolipid regulation and how sphingolipid signaling influences metabolic diseases. Progress in this area may contribute to new understanding and therapeutic options in complex diseases such as atherosclerosis, diabetes, metabolic syndromes and cancer.